Residing in a low-income-low-food-access neighbourhood and asthma in early and middle childhood in the Environmental influences on Child Health Outcomes (ECHO) program: a multisite cohort study - Yeyi Zhu; Emily A Knapp; Li Luo; Carlos A Camargo; Maria Gloria Dominguez-Bello; Holly B Schuh; Kohei Hasegawa; Qi Zhao; T Michael O’Shea; Irva Hertz-Picciotto; Aruna Chandran; Margaret R Karagas; et al. (BMJ Open)
Importance Access to healthy and affordable foods may play a role in reducing inflammation and in healthy pulmonary immune system development.Objective To investigate the association between residing in a low-income and low-food-access (LILA) neighbourhood and risk of childhood asthma. A positive association was hypothesised.Design, setting and participants This prospective cohort study consists of 16 012 children from 35 longitudinal studies in the Environmental influences on Child Health Outcomes programme (children born 1998–2021) from across the contiguous USA. We conducted survival analyses adjusted for child sex, race/ethnicity, maternal education, gestational smoking, and parental history of asthma.Exposure(s) Several commonly used geospatial food access metrics were linked to residential locations including: LILA census tracts where the nearest supermarket is >1 mile in urban and >10 miles in rural areas (LILA1 and 10), >1 mile in urban and >20 miles in rural areas (LILA1 and 20), >0.5 mile in urban and >10 miles in rural areas (LILA0.5 and 10), and >0.5 mile without a vehicle or >20 miles (LILAvehicle). Each metric was linked to lifetime residential history timelines then dichotomised according to whether the child had spent at least 75% of their life living in a LILA area separately for birth through age 5 years (cumulative early childhood) and birth through age 11 years (cumulative middle childhood).Main outcomes(s) and measure(s) Asthma incidence in cumulative early and middle childhood.Results Residing in a LILA0.5 and 10 and LILAvehicleneighbourhood was associated with a higher asthma incidence in cumulative early and middle childhood. The LILA0.5 and 10 and LILAvehicle associations were stronger for asthma during cumulative early childhood, where we observed hazard ratios of 1.13 (95% CI 1.02 to 1.24) and 1.13 (95% CI 1.01 to 1.27), respectively. The associations were higher among children who were Hispanic, were female and had lower maternal education.Conclusion and relevance Limited residential food access was associated with higher childhood asthma incidence, especially among female and Hispanic children and those with lower maternal education. Our findings support multipronged efforts to increase access to healthy and affordable food options and lower food insecurity in LILA neighbourhoods.